2016
DOI: 10.1007/s10853-016-0374-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale morphological characterization of process induced heterogeneities in blended positive electrodes for lithium–ion batteries

Abstract: The 3D morphology of LiNi1/3Mn1/3Co1/3O2 (NMC), LiFePO4 (LFP) and blended NMC/LFP electrodes envisioned for electric vehicles Li-ion batteries is characterized by both synchrotron X-ray tomography and FIB/SEM tomography. The size distribution of the active materials, the carbon phase and the pores, the specific surface area of the different solid phases, the concentration variations of the various phases through the total electrode thickness (X-ray tomography) or in smaller volumes (FIB/SEM tomography) are qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 61 publications
(54 reference statements)
1
30
0
Order By: Relevance
“…However, due to the homogeneous model structure, the complex influence of the ECA network cannot be addressed in detail. The 3D microstructure models can be based on artificial structures or can reconstruct structures from, e.g., focused ion beam (FIB) scanning electron microscopy (SEM) images . The latter is limited by difficulties to capture the ECA network and yet has only been applied to LIBs with liquid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the homogeneous model structure, the complex influence of the ECA network cannot be addressed in detail. The 3D microstructure models can be based on artificial structures or can reconstruct structures from, e.g., focused ion beam (FIB) scanning electron microscopy (SEM) images . The latter is limited by difficulties to capture the ECA network and yet has only been applied to LIBs with liquid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…In the real situation of manufacturing battery electrodes, it has been reported that, as the solvent evaporates in the drying process during fabrication of the electrode, the smaller particles tend to be located at the surface of the electrode film, the surface that will face the separator. 43 This particle distribution is the opposite of the desired configuration. Our results suggest that controlling the drying speed is important for uniform particle distribution during the solidification process of the electrode.…”
Section: Discussionmentioning
confidence: 96%
“…The intrinsic properties include e. g. the rate constant and the lithium diffusion coefficient in the solid host materials. Extrinsic properties are related to the composition and morphology of the electrode (e. g. particle size, electrode thickness, porosity), which significantly affect the charge transport properties of the composite (e. g. electrolytic conductivity, electronic wiring) as recently demonstrated by Besnard et al ,…”
Section: Figurementioning
confidence: 95%
“…The intrinsic properties include e. g. the rate constant and the lithium diffusion coefficient in the solid host materials. Extrinsic properties are related to the composition and morphology of the electrode (e. g. particle size, electrode thickness, porosity), which significantly affect the charge transport properties of the composite (e. g. electrolytic conductivity, electronic wiring) as recently demonstrated by Besnard et al [13,14] In this study, we show that the current responses from the individual constituents of a blended insertion electrode can be separated by using a special experimental setup. The approach enables the deconvolution cyclic voltammograms of the blend at different scan rates allowing: * The assignment of redox peaks * The identification of kinetic limitations * The observation of internal dynamics…”
mentioning
confidence: 99%